A definição de termos técnicocientíficos no âmbito dos estudos de terminologia (Revista de Estudos da Linguagem, 2003)
This article focusses on apprehending the nature and functioningof the terminological definition (DT), observed beyond the limitsof the categories of genus proximum and differentia specifica. Thearticle concludes that the recognition of the defining utterancerelated to the meaning environment of the scientific languagesinvolved is important, showing that the definition is amultidimensional textual object, with features that make it exceedthe more usual or traditional limits of a categorical-logical object.Furthermore, the study demonstrates that a strict a priori separationbetween concepts and meanings is not functional.